Punjabi as an Official Mother Tongue Language in Singapore Education System. - Bilveer Singh (2009)
Punjabi language has since long been part of the language landscape in Singapore. It was privately taught even though students could take it as a ‘third language’ . Following the adoption of the Goh report in 1979, the academic importance of mother tongues was institutionally sanctioned. While this focus fitted with national objectives, the Sikhs, being native Punjabi speakers, found it difficult to cope with the new emphasis, leading to negative consequences as far as performance in schools was concerned. This was because Sikh students were mainly taking Malay as their mother tongues with few opting for Mandarin, the other second languages besides Tamil. The Sikh community, together with other non-Tamil Indians organised themselves and pressured the government, culminating in the introduction of non-Tamil Indian languages in the national education system. This paper examines the evolution of Punjabi as a mother tongue since then and how it has impacted upon the community as a whole. How the community, in collaboration with the government, got the Punjabi language programme started and what have been its achievements and shortcomings, are analysed in this paper